Morphokinetic characteristics of embryos originating from extremely small follicles: A prospective study. (July 2019) - Avraham, Sarit; Kalma, Yael; Azem, Foad; Zakar, Liat; Amir, Hadar; Rahav, Roni; Barzilay, Lili; Dviri, Michal; Almog, Benny
Abstract: Objective: To investigate the developmental potential of oocytes and embryos derived from extremely small follicles (<10 mm) in comparison to those originated in larger follicles. Study design: A prospective study, undertaken in a university affiliated single center tertiary hospital. The study included 98 patients undergoing infertility treatments. On the day of ovum pickup (OPU) follicles were counted and measured. Aspiration of follicles larger and smaller than 10 mm was undertaken separately and the development of embryos originating from oocytes from these follicles was followed up using different wells for each embryo. There was no low limit of size for aspiration. Each oocyte retrieved was marked for its origin and numbered for further follow up. We recorded: Oocytes retrieved, maturation stage, fertilization rate, cleavage rate, morphokinetic parameters, embryo transfers, embryo freezing, oocyte freezing and biopsy rate for preimplantation genetic diagnosis (PGD). Quality was evaluated by the morphokinetic parameters of the embryos developed using time-lapse imaging technology. Day 3 KIDScore was calculated to all embryos. Results: Small follicles compared to large follicles displayed lower recovery rate (45% vs. 74%, P < 0.0001), fewer matured oocytes (37.5% vs. 61.7%, P < 0.0001), higher rates of GV oocytes (20.7% vs., 3.7%, P < 0.0001), and lower fertilization rate (43.7% vs. 63.3%, P < 0.0001. However, morphokinetic variables were similar between embryos that originated from either small or large follicles. Median KIDscores were identical for embryos from small or large follicle origin. Conclusions: Embryos originated from small follicles were not different than embryos from larger follicles, as assessed by morphokinetic parameters in time lapse system. In view of our findings, physicians should bear in mind that small follicle aspiration might yield good quality embryos.